Agronomic and ecological studies on the potato (Solanum tuberosum L.) in Southwest China : seed and crop management - He, W. (1997)
Potato is an important crop in sub-tropical Southwest China, where it is double-cropped in diverse ecological systems. Yields are higher at higher elevation. Spring crops show higher yields but lower light use efficiencies than autumn crops, especially at higher altitudes. The gaps between the actual and potential yields are mainly due to insufficient utilization of radiation and low light use efficiency of the actual crops. Earlier planting in spring increased yield at 500 m asl. At 1200 m asl effects of planting time on yield were absent. In autumn, these effects were generally absent at all elevations, although plant stands were consistently and often severely reduced by early planting. For spring crops, seed tubers should be older at lower altitude and younger at higher altitude than those commonly used. For autumn crops, seed tubers should be relatively old, both at low and high altitudes. Manipulation of seed sources can be done through selecting progenies of previous spring or autumn crops produced either at low or high altitudes, or from early harvest of the seed crop. The observed long-term after-effects of seed origins may have been associated with (unknown) effects on seed health. Heavier seed tubers gave higher yields in all conditions in the range from 20 to 124 g. When numbers of sprouts were set equal per unit area, the effect of weight of seed tubers on final tuber yield per unit area was absent. Tuber numbers per stem increased as seed tuber weight decreased when the seed tubers used were young. Cutting of seed tubers generally promoted plant emergence and increased stem numbers per plant in comparison with the whole seed tuber, per unit seed weight planted; cutting also spread a wilting disease probably mainly caused by Pseudomonas solanacearum, especially at lower altitude. The results of seed or plant density in combination with the effects of planting time, seed tuber weight and intercropping showed that a denser spacing up to 10 seed tubers/m 2consistently increased tuber yields. Plant stand was reduced by higher seed density in most experiments, but not at the expense of yield. Higher total yield of combined potato and maize was obtained when one row of maize was alternated with two rows of potato than when two rows of maize were alternated with two rows of potato. Results suggest that planting dates of the two species can be more closely synchronized in the current intercropping system, to achieve a more efficient use of space and time. Viruses, late blight and bacterial wilt caused varying degrees of yield loss in Sichuan, and they were closely associated with a number of biotic, abiotic and agronomic factors. Varietal resistances to the diseases, especially to late blight and bacterial wilt, were found. Parasitic nematodes were found in variable population densities. Defoliation by 28-spot beetle sometimes was severe. This thesis provides some basic information on crop production and agronomic measures required for further crop improvement in this complex agro-ecological region.